Advertisement Remove all ads

Show that the Sum of (M + N)Th And (M – N)Th Terms of an A.P. is Equal to Twice The Mth Term. - Mathematics

Show that the sum of (m + n)th and (m – n)th terms of an A.P. is equal to twice the mth term.

Advertisement Remove all ads

Solution

Let a and d be the first term and the common difference of the A.P. respectively.

It is known that the kth term of an A. P. is given by

ak = a + (k –1) d

∴ am + n = a + (m + n –1) d

am – n = a + (m – n –1) d

am a + (m –1) d

∴ am + n + am – n = a + (m + n –1) d + a + (m – n –1) d

= 2a + (m + n –1 + m – n –1) d

= 2a + (2m – 2) d

= 2a + 2 (m – 1) d

=2 [a + (m – 1) d]

= 2am

Thus, the sum of (m + n)th and (m – n)th terms of an A.P. is equal to twice the mth term.

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

NCERT Class 11 Mathematics Textbook
Chapter 9 Sequences and Series
Q 1 | Page 199
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×